2022
DOI: 10.1007/s12325-022-02230-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Αb Εxterno MicroShunt for the Treatment of Glaucoma

Abstract: The surgical management of glaucoma has been revolutionized by the introduction of minimally invasive glaucoma surgery (MIGS). The various MIGS options aim to meaningfully lower intraocular pressure with a better safety profile than traditional glaucoma surgery. The key clinical attributes and the emerging potential of an ab externo MicroShunt (PreserFlo TM ) are reviewed in the context of published evidence and clinical experience. This novel MicroShunt consists of an 8.5-mm-long tube that is implanted in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
(78 reference statements)
0
6
0
1
Order By: Relevance
“…Recent results from a 12-month, open-label, retrospective study demonstrated no significant difference in lowering of IOP or use of medication between patients with POAG in the combined and PMS-only surgery groups [ 12 ]. Other studies have identified that combined surgery is a risk factor for surgical failure and the need for postoperative needling [ 20 ]. However, data on adverse events following the combined procedure show that most are mild in severity and resolve without medical treatment [ 12 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent results from a 12-month, open-label, retrospective study demonstrated no significant difference in lowering of IOP or use of medication between patients with POAG in the combined and PMS-only surgery groups [ 12 ]. Other studies have identified that combined surgery is a risk factor for surgical failure and the need for postoperative needling [ 20 ]. However, data on adverse events following the combined procedure show that most are mild in severity and resolve without medical treatment [ 12 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to establish whether the concentration of MMC played a role in the outcomes of these studies. Further trials are required to determine the most optimal MMC concentration that will increase the surgical success rate while ensuring no added complications from the usage of higher concentrations (Burgos‐Blasco et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Many experts consider today the PreserFlo Micro-Shunt the preferable MIGS drainage device [15][16][17]. However, double implantation of this type of tube has not been debated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, based on the residual aqueous humor outflow after 14 days of washout of IOP-lowering pharmaceutical therapy, a theoretical mathematical model was developed with which to predict the number of XEN45 Gel stents (Allergan, Dublin, Ireland)another MIGS drainage implant with a 45 µm wide lumenneeded to sufficiently lower IOP in an individual patient [13]. Today, growing evidence supports that the PreserFlo MicroShunt is efficient and safe in lowering IOP and many experts consider this the preferable MIGS drainage tube that is currently available [15][16][17]. Furthermore, recent studies have shown that the device creates a novel type of bleb with a distinct morphology in particular with the posterior episcleral fluid lake [12].…”
Section: Introductionmentioning
confidence: 99%